The effectiveness of the educational complexes method in teaching students the skills of the straight attack and the accuracy of the fencing weapon. - Muhammad, Asst.L.Duaa Fawzi; زانستەکان, زانکۆی کوفە - کۆلێژی پەروەردەی وەرزشی و (Sulaimani Journal for Humanities, 2026)
This research aims to identify the effectiveness of the learning clusters strategy in teaching the straight attack and thrust accuracy skills in fencing to students, and to determine the superiority of this strategy over the traditional command-based approach. The researchers employed an experimental design with two equivalent groups. The study was conducted on a sample of 20 students from the College of Physical Education at the University of Kufa. The sample participated in learning clusters over a period of six weeks. - The researchers used an experimental design with two groups: an experimental group and a control group, and administered pre- and post-tests. - The research population consisted of third-year students from the College of Physical Education and Sports Sciences at the University of Kufa during the 2024-2025 academic year. - The field research procedures included describing the tests for the skills under study and using a pilot study to evaluate the effectiveness of the tools and the research team. The researchers concluded that the learning clusters approach had a positive impact, as it utilized diverse methods to teach the straight attack and thrust accuracy skills to the students. 1- The researchers recommend working on organizing the content of the course material with an educational design in accordance with the steps of the educational models strategy and in a way that is compatible with achieving the educational goals set in other sports activities.
Keywords: Educational complex strategy; my skills straight attack and accurate stabbing